A SODIUM HYALURONATE OPHTHALMIC SOLUTION FOR REDUCING DRY EYE AND ENHANCING CORNEAL WOUND HEALING AFTER PHOTOREFRACTIVE KERATECTOMY (PRK) - Kasetsuwan, Ngamjit; Reinprayoon, Usanee (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The objective of this work was to evaluate the efficacy and safety of 0.3% sodium hyaluronate (SH) versus hydroxypropyl-methylcellulose (HPMC)/dextran in reducing dry eye symptoms, recovering tear film function and enhancing corneal wound healing in patients who underwent photorefractive keratectomy (PRK) surgery. Methods: This was a randomized, masked-assessor, controlled, parallel-group and Phase II trial. 24 patients received 1 drop of 0.3% SH or HPMC/ dextran into each eye every 2 hrs during the first month after surgery, then as needed until the day (D) 168. Efficacy and safety criteria were assessed during six follow-up visits (D1, D3, D7, D28, D84 and D168). Results: About 0.3% SH caused a greater improvement than control in half of the efficacy criteria, including symptoms intensity and frequency, comfort of the eye drops, corneal haze, Schirmer I test, fluorescein and rose Bengal staining. At D28 and D84, a statistically significant difference favoring 0.3% SH was demonstrated for fluorescein corneal staining (p=0.0114 and p=0.0308, respectively). At D3, completed re-epithelization of the cornea was observed, 98% and 96% in 0.3% SH and control group respectively. The overall results for each of the measures used to assess the safety indicated that 0.3% SH had an excellent safety profile over 168 days of treatment. Conclusion: About 0.3% SH is a safe and effective treatment in reducing dry eye and enhancing corneal epithelial wound healing after PRK surgery. Keywords: Dry eye, Artificial tears, Sodium hyaluronate, Ocular lubricants, Refractive surgery, Photorefractive keratectomy.